Hasil Belajar IPA Siswa SD di Daerah Tertinggal dengan Penerapan Model Pembelajaran Inkuiri Terbimbing - Ricardus Jundu; Pius Herman Tuwa; Rosnadiana Seliman (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2020)
This study aims to determine the effect of the use of guided inquiry methods on students' science learning results at SDI Wae Ratun. This school is one of the schools in underdeveloped regions. This type of research is a quasi-experimental study with posttest only control group design research. The subject of the study was the fifth-grade students with sampling techniques using random class techniques. The sample chosen in this study was class V B as the experimental class and class V A as the control class. The instrument used is a test in the form of multiple-choice questions. Data analysis uses descriptive and inferential statistics. The results of data analysis obtained the calculation of tcount = 4.940 and ttable = 2.026 at a significant level and degrees of freedom = 35. Thus, there is a substantial influence on the use of guided inquiry learning models on student science learning results at SDI Wae Ratun.